ASSA14-12-08 POLY (ALGINATE-CALCIUM) MICROSPHERES LOADED WITH THROMBIN: A NEW HEMOSTATIC EMBOLIC MATERIAL FORTRANSCATHETERARTERIAL EMBOLIZATION. (1st December 2014) - Rong, JJ; Liang, M; Xuan, FQ; Sun, JY; Zhao, LJ; Zhen, HZ; Tian, XX; Liu, D; Zhang, QY; Peng, CF; Yao, TM; Li, F; et al.
Abstract : Objective: To date, transcatheterarterial embolization (TAE) has become a standard treatment to control intracavitary bleeding as an alternative to surgery. Due to excellent biocompatibility and no residual in vivo, biodegradable embolic materials are ideally preferred in TAE. However, only gelfoam is the commercially available biodegradable embolic material used in treating blunt trauma of solid abdominal viscera until now. And its stability and reliability are controversial in the past five decades. Thus, our team put forward an idea producing a new hemostasis embolic material: Thrombin loaded Alginate Calcium Microspheres (TACM), and the physical and pharmacological properties of the TACMs were also examined in this study. Methods: Alginate and thrombin were used to synthesise TACMs, which merged the advantages of conventional embolic microspheres and thrombin for treating blunt trauma of substantiality abdomen viscera by TAE. The TACMs were prepared using electrostatic droplet technique under mild conditions. The size distribution, morphology, pharmacological characteristics, changes to thrombus strength, cytotoxicity and systemic toxicity of the TACMs as well as the in vivo feasibility of embolization hemostasia for substantiality abdomen viscera was investigated. Results: The thrombin was successfully loaded in microspheres with high encapsulation efficiency and drug loading capacity. The release profile of TACMs was burst effect at early stage and sustained release later on, with the activity of thrombin preserved well. The strength of mixed thrombus, which was used as embolic agent in this research, increased in a dose dependent manner after TACMs were added. In addition, the TACMs were verified to be no cytotoxicity and systemic toxicity, and they were biodegradable in vivo . Finally, the results of preliminary applications revealed that the TACMs could serve as an effective and promising embolic material for blunt trauma and haemorrhage of solid abdominal viscera. Conclusion: TACMs can be used as another biocompatible, effective and reliable embolic agent for blunt trauma of substantiality abdomen viscera except gelfoam.